Electronic textbooks advantages and challenges for the Hellenic higher education and publishing community. Issue 6 (26th August 2014) - Kouis, Dimitrios; Konstantinou, Nikolaos
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to study advantages and challenges of electronic academic textbook (e-textbook) for the Hellenic higher education and the publishing community. In the higher education domain, the shift to e-textbook adoption entails numerous benefits. However, reluctance is noted in students as well as in publishers, impeding the faster realisation of this change. Decision-makers (such as the Ministry of Education and university administrations) need actual survey data to plan and perform the best strategy plan for the transition to the e-textbook era. Design/methodology/approach – Two different surveys took place among higher education students and academic textbook publishers in Greece. More specifically, the purpose of these surveys was twofold: first, to identify both students' and local publishers' views towards the e-textbooks as the near-future successor of printed books. Second, the results of the in-depth study will enable the proposal of certain solutions for the Hellenic higher education textbook system, which has reached an economic and functional deadlock. Our findings will also be easily adopted by other similar educational system across Europe. Findings – Our findings reflect a situation where e-textbooks will replace the printed books, but not in the near future, as both technology providers and publishers have to overcome many technical obstacles. Students are expecting the transition to occur soon, but still remain very reluctant about the inconvenience which might be caused to their reading habits. Originality/value – The results are unique and in alignment with similar surveys in other educational systems.